One Health landscape in Zimbabwe: Current status, challenges and opportunities for institutionalisation - Matope, Gift; Mugabe, P.H.; Kapungu, F.; Marimo, S.; Nys, Hélène M. de; Knight-Jones, Theodore J.D.; Caron, Alexandre; Richards, Shauna; Chirenda, Joconiah (CAB International, 2024)
A baseline assessment was conducted to describe the current landscape and opportunities for operationalising One Health (OH) in Zimbabwe. A desktop review, focus group discussion and key informant interviews were used to collect data. A predetermined analysis and reporting format including sections on research and innovation, governance, education and implementation in Zimbabwe was used. Key informants and focus group discussants were selected from senior experts from government, academia, parastatals and private organisations. The study revealed that the current OH governance structure focused on antimicrobial resistance (AMR), implemented predominantly by government ministries, with minimal coordination of initiatives across other sectors. The governance was coordinated through the OH Secretariat that was established in 2022 by the three ministries involving human health, agriculture and environment. To improve the governance and operationalisation of OH activities, a holistic transdisciplinary governance structure was proposed to be anchored at a higher level in Government. Except for eight higher education institutions that offer OH-related courses and/or programmes, OH education was not firmly embedded into the curricula of the different tiers of the education sectors in the country. While OH research data and publications were available on zoonotic diseases (brucellosis, anthrax, plague, rabies and salmonellosis), AMR and holistic-planned grazing approach, the research activities were mainly sector-based. The areas that were identified as priority for research and innovation for Zimbabwe include neglected tropical diseases, food safety, zoonotic diseases and environmental health. The institutionalisation of OH would be required to strengthen the coordination, governance and long-term sustainability of implementation.